Clinical and Recent Patents Applications of PD-1/PD-L1 Targeting Immunotherapy in Cancer Treatment—Current Progress, Strategy, and Future Perspective - Guo, Libin; Wei, Ran; Lin, Yao; Kwok, Hang Fai (Frontiers in Immunology, 2020)
Targeting PD-L1 and PD-1 interactions is a relatively new therapeutic strategy to treat cancer. Inhibitors of PD-1/PD-L1 include peptides, small molecule chemical compounds, and antibodies. Several approved antibodies targeting PD-1 or PD-L1 have been patented with good curative effect in various cancer types in clinical practices. While the current antibody therapy is facing the developing bottleneck, some companies have tried to develop PD-L1 companion test to select patients with better diagnosis potential. Meanwhile, many companies have recently synthesized small molecule inhibitors of PD-1/PD-L1 interactions and focused on searching novel biomarker to predict efficacy of anti-PD-1/PD-L1 drug. This review summarized clinical studies and patent applications related to PD-1/PD-L1 targeted therapy and also discussed progress in inhibitors of PD-1/PD-L1.